Stress fractures during top-level international athletics championships - Edouard, P.; Vinther, A. (British Journal of Sports Medicine, 2021)
Background Stress fracture is a frequent injury among athletics athletes. During international Athletics championships, although stress fractures represented a small percentage of all injuries (2.9% of all injuries and 4.9% of in-competition time-loss injuries for female athletes), it exists and should not be neglected, because it could be one symptom of Relative Energy Deficiency in Sport.